A review of recovery technologies of rare and rare earth metals from wastes generated in titanium and magnesium production - Merkibayev, Y. S.; Baigenzhenov, O. S.; Turan, M. D.; Kurbanova, B.; Toishybek, A. M. (Inst Metallurgy & Ore Beneficiation, 2023)
It is acknowledged that titanium and magnesium production wastes pollute the environment, which in the sequence they create an environmental hazard for soils, groundwater and vegetation. Meanwhile, these wastes can be considered secondary resources of rare and rare earth metals. In recent years, the processing of industrial waste has been a new trend for the extraction of rare and rare earth metals, which can partially cover the demand in case of their disposal. This article is devoted to a review of the available literature and articles on the extraction of rare metals from titanium-magnesium production waste using various processing methods. Methods of their utilization are discussed with an emphasis on the extraction of rare and rare earth metals. This review considered waste processing technologies of various pyrometallurgical and hydrometallurgical processes. Technological schemes of various leaching and extraction processes were presented to give a holistic view of waste processing and extraction of rare metals contained in them. In general, the article contains an overview of the works published on the extraction of rare metals, such as REE (rare earth elements), niobium, tantalum and vanadium.
Keywords: titanium wastes; rare metals; niobium; vanadium; scandium; rare earth elements; leaching; chlorination